Preventive potentials of piperlongumine and a Piper longum extract against stress responses and pain - Yadav V.; Chatterjee S.S.; Majeed M.; Kumar V. (My University, 2025)
Aim To compare stress resistance increasing and analgesic activities of piperlongumine and a methanolic Piper longum fruit extract (PLE). Methods Efficacies of a single and repeated daily oral doses (1–256 mg/kg/day) of PLE, piperlongumine, and 50 mg/kg/day doxycycline against foot shock stress triggered alteration in body weights and core temperatures, and of their 11 daily doses on antidepressants like activity in tail suspension test and on pentobarbital induced sedation in male mice were compared. In another experiment, analgesic activities of single and repeated daily 5 mg/kg oral doses of piperlongumine and PLE in mice hot plate test and in acetic acid induced writing tests were compared with those of aspirin and doxycycline. Results After their single oral doses no effects of piperlongumine or PLE or doxycycline were observed in the footshock stress induced hyperthermia test or in hot plate test. However, significant effects of piperlongumine and PLE in both the tests were observed after their 5 or more daily doses. Both of them also dose dependently suppressed daily handling and repetitive testing triggered alterations in body weights and core temperatures. Their doxycycline like antidepressant activity in tail suspension test and aspirin like analgesic effects in acetic acid writhing test were observed after their 11 daily 5 mg/kg oral dose. Conclusion Piperlongumine is another bioactive secondary metabolite of P. longum and other plants of piper species with stress response suppressing, analgesic, and anti-inflammatory activities. Its bactericidal activities can also contribute to its therapeutically interesting bio-activity profile. © 2016 Center for Food and Biomolecules, National Taiwan University